2003
DOI: 10.1007/s00239-002-2403-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Ecological Correlates of Intraspecific Variation in Pitviper Venom Composition Detected Using Matrix-Assisted Laser Desorption Time-of-Flight Mass Spectrometry (MALDI-TOF-MS) and Isoelectric Focusing

Abstract: The ability to detect biochemical diversity in animal venoms has wide-ranging implications for a diverse array of scientific disciplines. Matrix-assisted laser desorption time-of-flight mass spectrometry (and, for comparative purposes, isoelectric focusing) were used to characterize venoms from a geographically diverse sample of Trimeresurus stejnegeri ( n < 229) from Taiwan. Previously unrealized levels of heterogeneity were detected in venom phospholipase A(2) isoforms (PLA(2)) and in whole venom profiles. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 50 publications
5
79
1
3
Order By: Relevance
“…Significantly less dramatic variations in the peptide complement of injected venoms have been reported for several other organisms, including snakes (Chippaux et al, 1991;Creer et al, 2003;Daltry et al, 1996a,b;Francischetti et al, 2000;MacKessy et al, 2003;Monteiro et al, 1998a,b), spiders (Binford, 2001;Cristina de Oliveira et al, 1999;Escoubas et al, 2002) The α-, ω-conotoxins and s4a have all been previously isolated from the DV and characterized. Underlined peptides are those that are putatively identified in this work by mass matching to published cDNA sequences with predicted modifications.…”
Section: Conus Catus As Determined By Maldi-msmentioning
confidence: 93%
See 1 more Smart Citation
“…Significantly less dramatic variations in the peptide complement of injected venoms have been reported for several other organisms, including snakes (Chippaux et al, 1991;Creer et al, 2003;Daltry et al, 1996a,b;Francischetti et al, 2000;MacKessy et al, 2003;Monteiro et al, 1998a,b), spiders (Binford, 2001;Cristina de Oliveira et al, 1999;Escoubas et al, 2002) The α-, ω-conotoxins and s4a have all been previously isolated from the DV and characterized. Underlined peptides are those that are putatively identified in this work by mass matching to published cDNA sequences with predicted modifications.…”
Section: Conus Catus As Determined By Maldi-msmentioning
confidence: 93%
“…Sequence s4b is not included in this and Her, 2000). Variation of the peptide profiles of these other venomous animals has been associated with sex (Binford, 2001;Cristina de Oliveira et al, 1999;Escoubas et al, 2002), diet (Daltry et al, 1996b), age (Escoubas et al, 2002), geography (Binford, 2001;Creer et al, 2003), season (Monteiro et al, 1998b) and venom regeneration time (Pimenta et al, 2003). Studies controlling many of these factors have still observed venom variation, implying that intraspecific differences can be a result of genetic as well as environmental factors (Daltry et al, 1996a;Francischetti et al, 2000;Kalapothakis and Chavez-Olortegui, 1997;Monteiro et al, 1998a,b).…”
Section: Conus Catus As Determined By Maldi-msmentioning
confidence: 99%
“…As a whole, these results point out to a high degree of intraspecific variability in the expression of phospholipases A 2 in L. muta venoms. Intraspecific variability of PLA 2 loci has been reported in other viperid (Vipera palestinae [51]) and crotalid (B. asper [52]; Trimeresurus flavoviridis [53]) species, and this phenomenon is often linked to differences in diet among populations [53,54]. Snake venom phospholipase A 2 genes are members of a large, rapidly-evolving multigene family with many diverse functions.…”
Section: Moleculesmentioning
confidence: 99%
“…Geographical variation of venom composition occurs in some snakes and is suggested to evolve in response to changes in diets [11,[15][16][17]. Cone snails (of the family Conidae) are predatory gastropods that use a venom primarily to capture prey.…”
Section: Introductionmentioning
confidence: 99%